Broom-type sorghum cultivars subject to planting densities: agroeconomic responses and forage potential - Mendes, Erika Vanessa Cardoso; Albuquerque, Carlos Juliano Brant; Monção, Flávio Pinto; Silva, Nailson Gonçalves da; Freitas, Rogério Soares de; Rigueira, João Paulo Sampaio; Silva, Pedro Henrique Ferreira da; Pereira, Maria Izabel Batista; Vieira, Emanuell Medeiros; Salles, Jussara Souza (Ciência rural, 2025)
Using panicle rachis to manufacture artisanal brooms and the leaf and stem to produce forage can be a viable solution to incentivize the broom-type sorghum crop (Sorghum bicolor L. Moench). However, fitting the most suitable sowing density to achieve top productivity is crucial. The objective of this study was to evaluate agroeconomic responses and chemical composition of broom-type sorghum cultivars (Dwarf IAC 10V50, IAC 10V60, and IAC 10V70) subjected to planting densities (80,000; 120,000, and 160,000 plants ha-1) conducting two trials at the same harvest season. Growing 80,000 plants ha-1 led to taller plants (2.73 m) and longer panicles (51.0 cm) likely because of the lower competition for resources (e.g., water and soil minerals), but the planting density did not affect other agronomic traits. Dwarf IAC 10V50 was shorter (2.30 m) than the others (2.70 m), displaying a lower dry matter yield. A higher concentration of total digestible nutrients was found in the leaves and stems of the Dwarf IAC 10V50 (569.7 g kg-1) compared to the others (525.4 g kg-1). Growing the IAC 10V70 led to a higher percentage of non-defected panicles and a higher gross income (US$ 3058.86 ha-1). Adopting planting densities of up to 160,000 plants per hectare is possible without significantly affecting agroeconomic responses and broom-type sorghum’s chemical composition. The Dwarf IAC 10V50 displays a great forage potential while the IAC 10V70 has the best traits for generating profit with broom manufacture. RESUMO: Utilizar a raque da panícula para fabricar vassouras artesanais e a folha e o caule para produzir forragem pode ser uma solução viável para incentivar o cultivo de sorgo-vassoura (Sorghum bicolor L. Moench.). No entanto, o ajuste da densidade de semeadura mais adequada é crucial para atingir a máxima produtividade. O objetivo do estudo foi avaliar respostas agroeconômicas e composição química de cultivares de sorgo-vassoura (sorgo-anão IAC 10V50, IAC 10V60 e IAC 10V70) submetidas a densidades de plantio (80.000; 120.000 e 160.000 plantas ha-1), conduzindo dois ensaios na mesma época de colheita. O cultivo de 80.000 plantas ha-1 resultou em plantas mais altas (2,73 m) e panículas mais longas (51.0 cm) devido a menor competição por recursos (e.g., água e minerais do solo), mas a densidade de plantio não afetou significativamente outras características agronômicas. O sorgo-anão IAC 10V50 foi mais baixo (2,30 m) do que os outros (2,70 m) e apresentou menor produção de matéria seca. Uma maior concentração de nutrientes digestíveis totais foi encontrada nas folhas e caules do sorgo-anão IAC 10V50 (569,7 g kg-1) do que nos demais (525,4 g kg-1). O cultivo do IAC 10V70 resultou em uma maior porcentagem de panículas não defeituosas e maior renda bruta (US$ 3.058,86 ha-1). É possível adotar densidades de plantio de até 160.000 plantas por hectare sem afetar significativamente as respostas agroeconômicas e a composição química do sorgo-vassoura. O sorgo anão IAC 10V50 apresenta grande potencial forrageiro, enquanto o IAC 10V70 tem as melhores características para a fabricação de vassouras.